Comparing public policies impacting prescribing and medication management in primary care in two Canadian provinces. Issue 9 (September 2021) - Allin, Sara; Martin, Elisabeth; Rudoler, David; Church Carson, Michael; Grudniewicz, Agnes; Jopling, Sydney; Strumpf, Erin
Highlights: Polypharmacy and inappropriate prescribing are persistent health and policy challenges internationally. There has been limited policy attention targeting polypharmacy and inappropriate prescribing. Canada's two most populous provinces introduced team-based primary care models that include pharmacists. Policies related to prescribing and medication management also targeted quality improvement and information technology. The impacts of these policy changes on polypharmacy and inappropriate prescribing is not known. Abstract: The challenges of polypharmacy and inappropriate prescribing are recognized internationally. This study synthesizes and compares the policies related to these issues introduced in Canada's two most populous provinces – Ontario and Quebec – over the first two decades of the 21st century. Drawing on policy documents and consultations with experts, we found that while medication management to address polypharmacy and inappropriate prescribing has not been an explicit and consistent policy target in either province, some policy changes sought to directly or indirectly impact medication management. These changes include the introduction of primary care teams that include pharmacists, the introduction of a medication review performed by pharmacists (in Ontario), increased emphasis on quality improvement with some attention to potentially inappropriate medications (specifically opioids in Ontario), and investments in information technology to improve communication across providers and move toward electronic prescribing to improve medication safety and appropriateness. Despite growing evidence of the problem of polypharmacy and inappropriate prescribing, there has been limited policy attention targeting these problems directly, and policy changes with potential to improve prescribing and medication management may not have been fully realized. Further research to evaluate the impact of these changes on provider behaviours, and on patient outcomes, warrants attention.